1998
DOI: 10.1590/s0103-06631998000200003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação qualitativa do efeito de agentes de limpeza na camada de lama dentinária: estudo ultra-estrutural em microscopia eletrônica de varredura

Abstract: Quando qualquer instrumento abrasiona ou corta a dentina, produz na superfície uma camada de lama dentinária ou "smear layer". Dependendo do agente de união indicado em Odontologia adesiva, há a necessidade ou não da remoção da camada de lama da superfície dentinária. Com a finalidade de verificar a ação de diferentes substâncias para a limpeza dentinária, utilizamos 20 dentes pré-molares superiores íntegros, mantidos em soro fisiológico, nos quais as coroas foram seccionadas ao meio no sentido mésio-distal. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 4 publications
0
5
0
11
Order By: Relevance
“…The preparation of specimens followed the methodology proposed by Araújo et al . [2] with modifications in the production of smear layer [16]. The teeth were decontaminated with 0.2% solution of thymol (24 hours).…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of specimens followed the methodology proposed by Araújo et al . [2] with modifications in the production of smear layer [16]. The teeth were decontaminated with 0.2% solution of thymol (24 hours).…”
Section: Methodsmentioning
confidence: 99%
“…Nestas faces, com instrumento rotatório de aço carbide cilíndrico liso n 0 56, (KG Sorensen, Brasil), foi cortado aproximadamente 1mm de dentina em alta rotação, com refrigeração ar/água por 30 segundos, produzindo assim uma camada de esfregaço dentinário, sendo utilizada uma broca para cada dente, de acordo com o preconizado por Araújo et al(1998). 8 O própolis foi obtido de colmeias localizadas na região de Bauru, Estado de São Paulo. Após a limpeza, por meio de catação manual, preparou-se o extrato etanólico de própolis (EEP) com graduação do álcool etílico neutro a 70 0 G.L.…”
Section: At E R I a L E M éT O D O Sunclassified
“…This resulted from the adhesive system using 37% phosphoric acid to etch the dentin, which resulted in the complete removal of the smear layer, smear plugs, and dentinal tubule openings, in addition to demineralization of the peritubular and intertubular dentin. 19,20 Thus, the hydrophilic and hydrophobic monomers in the one-bottle Adper Single Bond 2 penetrated the demineralized dentin, forming a hybrid layer and resin tags with a triangular shape. 18,21 Perdigã o and Lopes 18 and Tay et al 22 reported that the etching technique with 37% phosphoric acid may have disadvantages because it could increase permeability, possibly leading to greater pulp irritation.…”
Section: Laser Effects On the Adhesive-dentin Interfacementioning
confidence: 99%